Analisis Perbandingan Sistem Hukum Pidana di Indonesia : Pidana Barat (KUHP) dan Pidana Adat - Arif Junaidi; Rizki Nurdiansyah (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
Indonesia has two frameworks of a criminal law system that runs in parallel, namely Western criminal law which comes from the Dutch colonial heritage through the Criminal Code (KUHP) and customary criminal law that develops in society based on traditional norms. Both have important positions in the national legal system despite their different characters and sources of legitimacy. The Criminal Code is present as a general written law with a strong codification and legal certainty, while customary criminal law is more flexible, dynamic, and emphasizes the value of social justice that lives in society. In practice, the application of customary criminal law is often oriented towards restoring harmony, deliberation, and family settlement. This is different from the Criminal Code which emphasizes formal sanctions in the form of imprisonment, fines, or other punishments that are retributive. This difference in orientation is what makes customary criminal law still relevant and accepted in various regions, even though it does not always receive full recognition in Indonesia's positive legal system. Along with the times, the government has drafted a Draft Criminal Code Bill (RUU KUHP) which is expected to be a form of national criminal law unification. The Criminal Code Bill from 2005 to the latest one in 2020 tried to incorporate elements of customary criminal law into the national legal framework. This aims to accommodate the legal pluralism that exists in Indonesia, as well as answer the needs of the community for a legal system that not only provides legal certainty, but also reflects a sense of social justice. Thus, the comparison between the Criminal Code and customary criminal law shows that there is tension as well as the potential for integration.